Design of linear polymer-based liquid lubricants by a strategy of complementary advantages. (16th January 2023) - Huo, Lixia; Guo, Jinshan; Yang, Fahu; Pan, Changou; Hu, Hanjun; Zhang, Kaifeng; Zhou, Hui; Liu, Peng
Abstract: Synthetic lubricating oils have attracted more and more interests due to their unique advantages. There are main two synthetic lubricating oils, poly-α-olefins (PAOs) and synthetic esters, while they each have strengths and weaknesses due to their specific molecular structures. Here, linear polymer-based liquid lubricants were designed via a strategy of complementary advantages, by esterifying the hydrogenated hydroxyl-terminated polybutadiene (HO-HPB-OH), with different saturated fatty acids (acetic acid, butanoic acid, octanoic acid and lauric acid). As lubricant base oil via overcoming one's weaknesses by acquiring others' strong points, ultralow friction and excellent wear-reduction performance were obtained with the proposed linear polymer-based liquid lubricants in comparison with the commercial PAO base oils, especially the dilaurate with the longer hydrocarbon chain length. Graphical abstract: Image 1 Highlights: Linear polymer-based liquid lubricants were designed by esterifying HO-HPB-OH. Integrating the advantages of PAOs and synthetic esters. Dilaurate possessed the ultralow friction and excellent wear-reduction performance.